How Much of the “Unconscious” is Just Pre – Threshold? - Fahle, Manfred W.; Stemmler, Torsten; Spang, Karoline M. (Frontiers in Human Neuroscience, 2011)
Visual awareness is a specific form of consciousness. Binocular rivalry, the alternation of visual consciousness resulting when the two eyes view differing stimuli, allows one to experimentally investigate visual awareness. Observers usually indicate the gradual changes of conscious perception in binocular rivalry by a binary measure: pressing a button. However, in our experiments we used gradual measures such as pupil and joystick movements and found reactions to start around 590 ms before observers press a button, apparently accessing even pre-conscious processes. Our gradual measures permit monitoring the somewhat gradual built-up of decision processes. Therefore these decision processes should not be considered as abrupt events. This is best illustrated by the fact that the process to take a decision may start but then stop before an action has been taken – which we will call an abandoned decision process here. Changes in analog measures occurring before button presses by which observers have to communicate that a decision process has taken place do not prove that these decisions are taken by a force other than the observer – hence eliminating “free will” – but just that they are prepared “pre-thresholdly,” before the observer considers the decision as taken.